Urinary Tract Complications in Abdomino - Pelvic Tumors: Round table on Urology held at the XXIX Uruguayan Congress of Surgery - Schiaffarino, Oscar; Cepellini, Raúl; Delgado, Hugo; Harretche, Martín; Rearden, Moisés (Cirugía del Uruguay, 1978)
The paper discusses the problems with which surgeons and gynecologists are faced when sorne sector of the urinary tract is affected by abdomino - pelvic tumJrs, mostly neoplasms of recto - sigmoid and genital organs. These complications may arise due to lesional extension of tumor, accidental lesion· during surgery or functional sequelae due to neurologic alteration. There is a review of studies which should be carried out prior to surgery in order to ascertain the condition of urinary tract and a listing o"f solutions for the different situations which may arise and which ineludes the use of prothesis.